PENINGKATAN PEMAHAMAN KESEHATAN MENTAL BAGI PETUGAS LEMBAGA PEMBINAAN KHUSUS ANAK KELAS II KOTA BENGKULU - Yahya Eko Nopiyanto; Diah Ayu Aguspa Dita; Dian Pujianto; Fiona Sarah Musfita; Zahra Putri Amelia; Mas’ullah Andriyani (Universitas Mataram, 2023)
The increasing prevalence of mental disorders in children at Special Child Development Institutions needs attention from various parties. However, much attention and concrete steps have not been taken by academics or practitioners to develop the potential that exists in children at Special Child Development Institutions. Moreover attention and concrete steps on the problem of child mental health disorders. The purpose of this community service activity is to increase the understanding of the Special Child Development Institution for Class II in Bengkulu City regarding the importance of mental health. Submission of workshop materials carried out by lecture method. The partners involved in this activity totaled 17 LPKA officers who came from the health sub-section, and the guidance and education sub-section. The implementation of community service activities took place at LPKA Class II Bengkulu City. The time for the workshop to be held is July 13, 2023. From the results of the implementation of the community service activities, it is known that the partners or officers of the Special Child Development Institute Class II in Bengkulu City welcomed this community service activity. Partners are enthusiastic to take part in the entire series of service activities. With this activity, the partners hope that there will be continuity of cooperation in the form of assistance so that the officers of the Special Child Development Institute not only have an understanding but also have the skills to identify mental disorders in children at LPKA Class II Bengkulu City.